An update on solid phase-supported liquid extraction. (September 2015) - Silvestro, Luigi; Savu, Simona Rizea
Solid phase-supported liquid extraction (SLE) is a technique almost 40 years old being rediscovered in the last few years due to its simplicity, optimal for automation and giving very clean extracts with minimal matrix effects when analyzed by techniques like HPLC–MS/MS, GC–MS/MS, CE–MS/MS. In the next paragraphs the evolution of SLE, according to literature, will be presented first, followed by some considerations on the SLE material now available and a typical protocol of work. To conclude, considerations based on the author's practical experiences with SLE will be done, as well as few remarks on potential future areas of SLE development.